2012
DOI: 10.1104/pp.111.188318
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Strawberry Fruit Aroma and Identification ofO-Methyltransferase FaOMTas the Locus Controlling Natural Variation in Mesifurane Content      

Abstract: Improvement of strawberry (Fragaria 3 ananassa) fruit flavor is an important goal in breeding programs. To investigate genetic factors controlling this complex trait, a strawberry mapping population derived from genotype '1392', selected for its superior flavor, and '232' was profiled for volatile compounds over 4 years by headspace solid phase microextraction coupled to gas chromatography and mass spectrometry. More than 300 volatile compounds were detected, of which 87 were identified by comparison of mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
191
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(218 citation statements)
references
References 91 publications
16
191
5
4
Order By: Relevance
“…Fruits can also synthesize volatile phenylpropenes that contribute to their aroma (Jordán et al, 2001;Aubert and Pitrat, 2006;Ortiz-Serrano and Gil, 2010). Eugenol production by ripe strawberry fruits has been reported previously (Pyysalo et al, 1979;Zorrilla-Fontanesi et al, 2012). Interestingly, the amount of this volatile is lower in cultivated fruits (F. ananassa) than in wild diploid Fragaria vesca (Pyysalo et al, 1979).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Fruits can also synthesize volatile phenylpropenes that contribute to their aroma (Jordán et al, 2001;Aubert and Pitrat, 2006;Ortiz-Serrano and Gil, 2010). Eugenol production by ripe strawberry fruits has been reported previously (Pyysalo et al, 1979;Zorrilla-Fontanesi et al, 2012). Interestingly, the amount of this volatile is lower in cultivated fruits (F. ananassa) than in wild diploid Fragaria vesca (Pyysalo et al, 1979).…”
supporting
confidence: 52%
“…It was shown that throughout the strawberry fruitripening process, eugenol accumulates in ripe receptacles (Pyysalo et al, 1979;Zorrilla-Fontanesi et al, 2012;Aragüez et al, 2013). The orthologous gene of FaEOBII in petunia (PhEOBII) has been shown to be involved in eugenol production (Spitzer-Rimon et al, 2010).…”
Section: The Expression Of Faeobii Is Highly Expressed In Ripe Fruitmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved genotyping capacity (Agarwal et al 2008) and VOC quantification methods (Tholl and Rose 2006) are now enabling the application of quantitative trait loci (QTL) analysis to aroma components. Several studies have addressed the identification of QTLs for VOCs in Rosaceae species as apple (Zini et al 2005;Dunemann et al 2009;Rowan et al 2009a), rose (Spiller et al 2010), and strawberry (Zorrilla-Fontanesi et al 2012) and in other plant species including tomato (SalibaColombani et al 2001;Tadmor et al 2002;Mathieu et al 2009;Zanor et al 2009), grape (Doligez et al 2006), melon (Obando-Ulloa et al 2008), rice (Amarawathi et al 2008), eucalypt (Henery et al 2007; O' Reilly-Wapstra et al 2011), and tobacco (Julio et al 2006). Conversely, no QTLs underlying peach fruit aroma have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, about 25 determine the typical peach aroma (Eduardo et al 2010): particularly γ-and δ-decalactone play a key role in association with C 6 compounds, aldehydes, aliphatic alcohols, esters, norisoprenoids, phenylpropanoids, and terpenes (Horvat et al 1990). Key genes associated with aroma production have been described in few plants, including strawberry and apple (Schwab et al 2008;Mathieu et al 2009;Battilana et al 2011;Dunemann et al 2011;Zorrilla-Fontanesi et al 2012), but little is known in peach.…”
Section: Introductionmentioning
confidence: 99%